Characterization and theoretical calculations of the T(Al20Cu2Mn3)/Al interface in 2024 alloys: TEM and DFT studies. (April 2023) - Li, Xianzhuo; Chen, Xia; Feng, Yifei; Chen, Bin
Abstract: In this study, we systematically investigated several typical interfaces of the T-phase (a precipitated phase in 2024 alloy), namely the T(200)/Al(403), T(101)/Al( 4 ‾ 03 ) and T(200)/Al(301) interface and analyzed interface properties through first-principles calculations and HAADF-STEM (High-angle annular dark-field scanning transmission electron microscope) observations. The calculation results show that AlMn- terminated interface is the most thermodynamically stable of the different terminal interfaces in T(200)/Al(403) and T(101)/Al( 4 ‾ 03 ) interface. Therefore, we also speculate that the T precipitated phase forms interface with aluminum matrix through the AlMn- terminated. By investigating the DOS(density of states) and the electron density difference of the interface, we prove that Al–Mn covalent bond is formed on the outer surface of the T phase. In addition, this work provides some basis for the analysis of the T phase and T/Al interface from an energy point of view through various data, which helps us to further investigate the properties of the interface. Highlights: Characterization of T(Al20 Cu2 Mn3 ) precipitated phases in 2024 aluminum matrix by HAADF-STEM and EDS mapping. For the first time and systematically, first-principle calculations were performed for different interfaces of T-phase, and their various properties were analyzed. Three different interface calculations show that the AlMn- terminated interface is the most thermodynamically stable. The ( 101 ) T / / ( 4 ‾ 03 ) A l interface is more stable.